Investigação do efeito alelopático dos extratos da aroeira-preta Myracrodruon urundeuva Freire Allemão no desenvolvimento das sementes das braquiárias Urochloa decumbens Stapf e Urochloa brizantha (Hochst. ex A. Rich) Stapf - Yoshioka, Jeniffer Miho (2021)
Brachiaria grasses have great importance in the livestock sector, however, these grasses are considered weeds that affect negatively the productivity of many crops. Field observations indicate that Myracrodruon urundeuva shows allelopathic effects on Urochloa species. However, there are no data on literature describing the allelopathic effects for different tissues of aroeira-preta, neither the classes of secondary metabolites involved on those interactions. In this study, the allelopathic effect of the crude extracts and fractions of leaves, branches, stems and roots of M. urundeuva was evaluated into seeds germination and seedlings growing of U. brizantha, U. decumbens and Lactuca sativa. Chemical composition of these extracts were analyzed by UHPLC-ESI-QTOF. This was the first study of aroeira-preta using the Global Natural Products Social Molecular Networking (GNPS) platform and Feature-Based Molecular Networking (FBMN) as metabolomics tools for compounds annotation. Fifty-five secondary metabolites, distributed in eight different classes of compounds, were annotated, which twenty were annotated for the first time for M. urundeuva. Crude extracts and fractions inhibited seeds germination and development. The ethyl acetate fraction of roots showed a higher activity, inhibiting seeds germination at concentrations of 100 and 50 mg/mL and roots development in all tested concentrations, i.e., 100, 50 and 25 mg/mL. This fraction was characterized by dimeric chalcones urundeuvines as their majoritary compounds.